Cognitive impairment in a sample of adult patients with multiple sclerosis: an Egyptian study - Sara Elbasuony Elshehawy; Ibtihal M. A. Ibrahim; Ayman Mohamed Abdel-Naby; Mohamed El-Husseini Khater (Middle East Current Psychiatry, 2023)
Abstract Background Multiple sclerosis is a chronic neuro-inflammatory disease of the brain and central nervous system. We aimed at assessing the cognitive functions present in adult patients with multiple sclerosis in remission phase of the disease comparing them to healthy control group. Results This is a cross sectional study using Penn Computerized Neurocognitive Battery (CNB) to measure performance accuracy and speed on specific neurobehavioral domains comparing MS group to healthy group. The MS group showed lower statistically significant difference in the accuracy of spatial memory, the motor speed, Non-verbal reasoning, Spatial orientation, social cognition, and working memory. Also, MS group showed statistically significant longer reaction time in facial memory, attention, spatial orientation, and non-verbal reasoning. Conclusions Attention, spatial orientation, non- verbal reasoning, Facial memory, working memory, social cognition and spatial memory were affected in patients with MS during their remission phase. cognitive evaluation should constitute a major part of the clinical examination in MS, especially when impairment seems likely.